10.0k views
5 votes
Who knows the answer plzz help​

Who knows the answer plzz help​-example-1

1 Answer

3 votes

Answer:

x = -3 +
(5√(2) )/(2), -3 -
(5√(2) )/(2)

Explanation:

Step 1: Isolate x's

2x² + 12x = 7

Step 2: Factor

2(x² + 6x) = 7

x² + 6x = 7/2

Step 3: Complete the Square

x² + 6x + 9 = 7/2 + 9

(x + 3)² = 25/2

Step 4: Solve for x

√(x + 3)² = √25/2

x + 3 = 5√2/2

x = -3 ± 5√2/2

User Mike Sprague
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.